Organizational Culture and Spiritual Leadership on Employee Performance (Case Study of Business Units at Darussalam Gontor University) - Alfin Aulia; Mohammad Zaenal Abidin (University of Darussalam Gontor, 2021)
Organizational culture is a perception made jointly by members of the organization and must be obeyed by members of the organization or it is called a system created for togetherness. This is used as a culture or culture that guides members of the organization in every day. Darussalam Gontor University Business Unit is one of the business fields owned by Darussalam Gontor University which has employees with different backgrounds. This study aims to analyze the influence of organizational culture and spiritual leadership on the performance of employees of the Business Unit of Darussalam Gontor University. This type of research is quantitative research with a total of 49 respondents. The population of this study were all employees of the Darussalam Gontor University Business Unit which included managers, staff and operational employees. The technique used is multiple linear regression analysis technique. Data obtained through respondents with a survey in the form of a questionnaire and measured using a Likert scale. The results show that organizational culture has a positive but not significant effect on employee performance. Meanwhile, spiritual leadership has a positive and significant effect on employee performance. Suggestions that can be conveyed from this study are (1) Darussalam Gontor University Business Units should always maintain and improve the factors that influence employee performance. (2) Evaluating factors that do not affect employee performance.